Pengaruh Biaya Produksi Dan Harga Jual Terhadap Volume Penjualan Pada Industri Roti Di Kota Padang - Nini Rostiana; Febryandhie Ananda (Pusat Riset dan Inovasi Nasional, 2023)
The intense competition between companies today, makes companies think even harder. The way the factory introduces its products to consumers, with the aim of luring buyers. These competing companies try to satisfy customers by making products that are needed and liked by consumers. To win the sales competition to increase the volume or level of sales. Not only sales volume, but also production and marketing costs have a huge impact on plant development and failure. This study aims to determine the effect of production costs (X1) and price (X2) on sales volume (Y) in the bakery industry in the city of Padang. Source of data used in this research is Primary Data. The data collection method used in this study was a questionnaire with a sampling technique in this study using a non-probability sampling technique. The data analysis technique in this study was multiple linear regression analysis using the SPSS program. Based on the results of testing the data shows that there is a positive and significant influence between production costs (X1) and price (X2) on sales volume.